The effect of different hydraulic retention tim (HRT) on biological pretreatment to chemical pulping - Siti Nur Nadzmiah, Mohd Nor (2006)
Low composition of lignin and high of cellulose contains showed that banana stem wastes one of good sources for pulping purpose. These materials are cheap and can easy to get, since banana was planted widely in Malaysia for commercial used. After its harvesting, the banana stem are cut and usually left in the soil plantation to be used as organic material where actually, this crops can be used for more rational way of utilization, namely as a sources of cellulosic fibre for pulping process. Common chemical pulping process that had been used nowadays in industry frequently bring harms to the environment and also to human life as it consume and produce much of chemical reagent. Thus, the purpose of biological pretreatment using mixed culture from banana soil plantation with different Hydraulic Retention Time (HRT) in this study is to reduce the amount of chemicals that will be used and produced from the chemical pulping process and also to reduce costs, energy consumption and time needed for the pulping process. The goal of biological pretreatment is to break lignin seal and disrupt the crystallize structure of cellulose in the banana stem waste and the different HRT that was used are 9, 19.5 and 30 days where it is believed that different HRT has its own effect to the treatment process. From the experiment, the maximum amount that can be degraded is about 5.5 % of lignin. The best HRT that been analyzed is HRT equal to 19.5 days. The treated banana stem showed the positive result in chemical pulping process where percentages of lignin reduced is higher than untreated banana stem wastes.